The function of stone tools from Gua Arca Site, Kangean Island, East Java: Fungsi alat batu dari Situs Gua Arca, Pulau Kangean, Jawa Timur - Rahfi Muhammad (BRIN, 2021)
Gua Arca is a prehistoric cave site in Kangean Island, East Java. Stone tools found in this site has yet to be studied in terms of the function, merely being collected instead. This article discusses the possible function of the stone tools based on typological and microscopical use-wear analysis, compared to the results from previous experimental research. The results of the analysis show that use-wear is related to the tools’ function and the material they worked on. The similarity between use-wear traces on stone tools from Gua Arca and the result from previous experimental research indicates the stone tools’ function as wood-working tools and food-processing tools.